Empowering Student Dormitory Laundry Businesses in Pusakamulya Village: A Strategic Professionalization for Enhancing Community Economic Quality - Rohman Pranoto; Isrun Abdurahman; Agus Salim; Irfan Alkhotiri; Rizaldy Alpiansyah (Al Musa’adah : Journal of Community Service STAI Minhajul Haq, 2026)
This study examines a community empowerment initiative focused on the professionalization of laundry businesses in Pusakamulya Village, Purwakarta. Despite the high demand from the local Santri (student) population, these SMEs often struggle with suboptimal management. Through a seven-day intensive mentoring program, a team from STAI Minhajul Haq implemented a management framework covering entrepreneurship, operations, and financial literacy. The results showed a significant increase in operational efficiency and service quality. This project underscores the importance of academic intervention in transforming rural micro-businesses into sustainable enterprises.